Access to pharmaceutical products in six European countries – analysis of different pharmaceutical distribution systems - Walter, Evelyn; Dragosits, Aline; Said, Monira (Farmeconomia. Health Economics and Therapeutic Pathways, 2012)
OBJECTIVES: The aim of the study was to draw a comprehensive picture of the pharmaceutical wholesale sector, outlining its socio-economic importance compared to different distribution systems such as short-line wholesaling, direct sales from manufacturers, Reduced Wholesale Arrangements (RWA) and Direct to Pharmacy (DTP) arrangements. Its role is considered from an economic, effectiveness and, most importantly, a public health viewpoint with qualitative and quantitative methods, focusing on France, Germany, Italy, the Netherlands, Spain and the UK. METHODS: First, data has been sourced from annual GIRP and IMS-Health statistics; second, a systematic literature research verified the empirical findings; third, an online-questionnaire was directed to pharmacies. Further data have been sourced from a questionnaire, addressing GIRP-full-member associations and wholesale companies (return rate 86%). RESULTS: On a weighted average, pharmaceutical full-line wholesalers in the observed countries alone pre-finance € 10.2 bn over a period of 41 days the entire medicine-market and secure the cash-flow of the social-insurers (Germany: € 2.60 bn for 38 days; Italy: € 2.27 bn for 68 days; the UK: € 1.48 bn for 36 days; France: € 1.28 bn for 22 days; Spain: € 969.76 m for 27 days; the Netherlands: € 399.09 m for 30 days on average). On average, pharmaceutical full-line wholesalers are bundling products of 18.28 manufacturers per delivery. The process costs would increase by € 164,922.43 to € 171,510.06 per year, if there were no pharmaceutical full-line wholesalers. These additional costs would have to be paid by manufacturers, pharmacies and finally by patients. Regarding the satisfaction with different distribution models, the results of the online-questionnaire show that pharmacists in the observed countries are very satisfied with the distribution through their pharmaceutical full-line wholesalers. CONCLUSIONS: The study showed that pharmaceutical full-line wholesalers have an important and unique position in the pharmaceutical supply chain. Special functions like the pre-financing of the entire medicinal product market, or the guarantee of the continuous supply of all medicinal products verify these findings.